Analisis Dampak Teknologi dan Digitalisasi terhadap Pulau Jawa Tahun 2015-2022 - Trio Toto Tanoyo; Setyo Wahyu Sulistyono (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The development of digital technology has resulted in significant transformation in various aspects of life, especially in the economic sector. A region's ability to obtain, utilize and process information has a major impact in stimulating increased economic growth. Despite technological advancements, not everyone benefits equally. The purpose of this study is to explore the role of digitalization in driving economic growth in a region, by utilizing secondary data from BPS for the period 2015–2022 using the panel data regression method. The research findings show that for smartphone users, the Human Development Index (HDI) has a significant positive impact on economic growth. The number of internet users has a significant negative impact on economic growth. On the other hand, the workforce shows that there is no significant influence on the economic growth of the province of Java.